2020
DOI: 10.1002/ejoc.202001409
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Transfer Catalytic Strategy: Rapid Synthesis of Spiro‐Fused Heterocycles, Integrated with Four Pharmacophores‐Succinimide, Pyrrolidine, Oxindole, and Trifluoromethyl Group

Abstract: An efficient and practical 1,3‐dipolar [3+2] cycloaddition of N‐2,2,2‐trifluoroethylisatin ketimines and maleimides has been achieved through phase‐transfer catalytic process by using the cheap quaternary ammonium salt as a catalyst. The strategy grants rapid generation of various complex trifluoromethyl spiro‐fused[succinimide‐pyrrolidine‐oxindole]s in good yields and with excellent diastereoselectivities. The preparative‐scale reaction in conjunction with the optimized Suzuki–Miyaura cross‐coupling derivatiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…When 1.0 equiv of TBAB was added to the DBU-catalyzed reaction, the reaction pathway changed to produce 4aa (44% yield), whereas only trace 3aa was detected (entry 3). This result strongly suggested that the carbonate ion of tetrabutylammonium carbonate and in situ generated ethoxy anion (EtO – ) underwent almost irreversible ion exchange during the reaction process, hence suppressing the formation of 3aa . It should be noted that the reaction rate of organocatalysis was much faster than that of PTC (15 min vs 2 h).…”
Section: Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…When 1.0 equiv of TBAB was added to the DBU-catalyzed reaction, the reaction pathway changed to produce 4aa (44% yield), whereas only trace 3aa was detected (entry 3). This result strongly suggested that the carbonate ion of tetrabutylammonium carbonate and in situ generated ethoxy anion (EtO – ) underwent almost irreversible ion exchange during the reaction process, hence suppressing the formation of 3aa . It should be noted that the reaction rate of organocatalysis was much faster than that of PTC (15 min vs 2 h).…”
Section: Results and Discussionmentioning
confidence: 94%
“…Based on previous literature, ,, controlled experiments, and dynamic high-resolution mass spectrometry (HRMS) studies, a plausible mechanism for the tunable cascade reaction was tentatively proposed (Scheme ). First, both organocatalyzed and phase-transfer/sunlight relay catalyzed cascade reactions were found to undergo the same two pathways to access key intermediate M3 : (i) the base assaults α-hydrogen atom at the diesters moiety of ureidomalonate 1a , and the conjugated addition of the carbanion to alkenyl azlactone 2a delivers M1 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…A highly practical phase transfer catalytic approach for the diastereoselective assembly of CF 3 -containing spiro-fused[succinimide-pyrrolidine-oxindoles] was reported by Chen and co-workers ( Scheme 6 ). 55 With the help of 5 mol% of quaternary ammonium salt tetrahexylammonium bromide (THAB) as the phase transfer catalyst and 2 mol% of Cs 2 CO 3 as the base, the respective products 13 derived from the [3+2] cycloaddition of N -2,2,2-trifluoroethylisatin ketimines 1 and maleimides 12 were accomplished in 69–99% yields with excellent diastereoselectivity (up to >99 : 1 dr) within a short duration of time. Investigations on the reactivity of ketimines with maleimides revealed that both N -H free and N -protected ketimines encompassing electron-deficient and electron-rich substances on diverse positions participated in the reaction very smoothly.…”
Section: Synthesis Of Spirocyclic Oxindoles Comprising Trifluoromethy...mentioning
confidence: 99%
“…A highly efficient and practical diastereoselective [3 + 2] cycloaddition reaction of N -2,2,2-trifluoroethylisatin ketimines 1 with maleimides 88 was reported by the Chen group in 2021 ( Scheme 37 ) [ 55 ]. This reaction affords a series of complex trifluoromethyl spiro-fused[succinimide-pyrrolidine-oxindole] derivatives 89 with good diastereoselectivities (67:33–>99:1 dr) in moderate to excellent yields (69–96%) in the presence of a phase transfer catalyst.…”
Section: Organocatalytic Reactions Involving N -22...mentioning
confidence: 99%